Pengaruh Motivasi Belajar Terhadap Kemandirian Belajar Siswa SMK Negeri 2 Kendari - Permata Sari, Rezky; Renata, Dian; Utami, Sri (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2022)
Learning autonomy is the ability of students to direct themselves to learn autonomously without any encouragement from other parties. On the other hand, it is suspected that students will not be able to achieve independent learning without having a strong learning motivation. In some literature it is found that the condition of learning motivation has the potential to have an influence on the birth of learning independence in students. This study aims to determine whether learning motivation affects the learning independence of students at SMK Negeri 2 Kendari. This research is a quantitative research with a survey type. The population in this study were all students of SMK Negeri 2 Kendari in the academic year 2021/2022 with a total of 558 students. The sample was estimated by random sampling technique. To determine the sample size, Slovin's formula is used with a degree of error of 0.05 so that the sample is 233 students. Data were collected through a scale of motivation and learning independence. Data were analyzed both descriptively and through inferential statistics. The results showed that: a) students’ learning motivation was in the medium category, b) students’ learning independence was in the medium category, and c) learning motivation had a significant influence on the learning independence of SMK Negeri 2 Kendari students.